(untitled) (Global Journal of Human-Social Science, 2023)
This document posits that the splintering of one language into many languages in Genesis 11 1-9 offers framework for interpreting linguistic differentials central to misunderstanding within U S -China interfacing and that matters associated with context are the most pressing This focus is on linguistic differentials central to misunderstanding not necessarily disagreement Matters of simple understanding are proving to be beyond reach and the ramifications are of theoretical and practical relevance Focus on this matter has foundation that goes beyond the histories of China and the U S and into biblical frameworks as manifested in Genesis 11 1-9